Pengaruh Corporate Governance Terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Intervening - Winanda, Dea Jenia; Yeni, Fitri; Sari, Putri Intan Permata (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2024)
The company becomes a measure to assess how well management manages future operational prospects. Thisl study aimsl to examine thel impact ofl the Independentl Boardl ofl Commissioners, Boardl lof Directors, andl Auditl Committee onl firml value withl Dividendl Policy asl an lIntervening lVariable. The purposivel sampling techniquel was usedl to selectl 24 manufacturingl companies inl the foodl and lbeverage sub-sectorl as research samples. The results showed that thel Independent Boardl of Commissionersl had nol significant impact onl dividend policy, while the Board of Directors and Auditl Committee had al significant effectl on dividend policy. Thel Independent Board ofl Commissioners andl the Auditl Committee havel no significantl impact on firm value, whilel the Boardl of Directorsl has al significant influencel on firm value. Overall, thel Independent Board ofl Commissioners, Boardl of lDirectors, and Auditl Committee do not show al significant impact onl firm value when Dividendl Policy acts asl an interveningl variable inl food andl beverage lsub-sector manufacturingl companies listed onl the Indonesial Stock Exchangel during the period 2018-2022.